1983
DOI: 10.1128/jvi.45.2.868-871.1983
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequence of the Long Terminal Repeat and Flanking Cellular Sequences of Avian Endogenous Retrovirus ev -2: Variation in Rous-Associated Virus-0 Expression Cannot Be Explained by Differences in Primary Sequence

Abstract: A fragment of chicken DNA containing the left long terminal repeat of endogenous retrovirus ev-2 and flanking cellular sequences has been molecularly cloned and analyzed. Comparison with sequence data from the analogous regions of ev-1 and Rous-associated virus-0 viral DNA reveals similarities among flanking regions of the integrated proviruses and among all three long terminal repeats. From the latter finding, we conclude that the difference in level of expression of ev-2 and its progeny Rous-associated virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The upstream site includes the binding site for EFI or FII (11,14,17,31,42) Sequence comparison of exogenous virus and ev U3 regions. The sequences of the exogenous virus (RSV) and ev (ev-2-RAV-0) U3 regions are from previously published sequences (20,21,39,41) and were independently confirmed. Vertical lines between the sequences represent regions of identity, while dots represent mismatches.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The upstream site includes the binding site for EFI or FII (11,14,17,31,42) Sequence comparison of exogenous virus and ev U3 regions. The sequences of the exogenous virus (RSV) and ev (ev-2-RAV-0) U3 regions are from previously published sequences (20,21,39,41) and were independently confirmed. Vertical lines between the sequences represent regions of identity, while dots represent mismatches.…”
Section: Resultsmentioning
confidence: 74%
“…The LTRs of the second class of avian retroviruses, the 1960 ZACHOW AND CONKLIN avian endogenous viruses (evs), are distinct from those of the exogenous viruses in that they lack a detectable associated enhancer (6-8, 30, 53). The absence of a strong enhancer in ev LTRs has been correlated with the low growth rate and low oncogenic potential of evs relative to exogenous viruses (53) as well 'as with major sequence differences between the U3 regions of these two virus groups (20,21,39,41). In particular, the ev U3 region is shorter than that of exogenous viruses, containing gaps in sequence as well as regions of sequence divergence that include sequences that correspond to the two 5'-most exogenous virus enhancer domains (the EFII, FIII, or al site and the Fl or a3 binding site) and to the RSV EFIII binding site.…”
mentioning
confidence: 99%
“…A comparison of the nucleotide sequences of avian retroviral LTRs shows that major differences exist between LTRs of exogenous and endogenous viral origin. Endogenous retroviral LTRs are relatively short (-277 base pairs [bp]) and are highly interrelated in sequence (20). The LTRs of exogenous retroviruses such as Rous sarcoma virus (RSV) and avian leukosis virus (ALV) differ significantly from the endogenous viral LTRs but show extensive sequence homology to one another (4).…”
mentioning
confidence: 99%
“…In addition, these proviruses can be activated in vivo by treating cells which contain them with nucleotide analogs such as bromodeoxyuridine (37) or 5-azacytidine (7,20). Under these conditions, ev-2 gives rise to an infectious virus called Rousassociated virus-0 (RAV-0); the LTRs of ev-2 and RAV-0 are identical (23,41). Previous studies have indicated that the expression of individual evs correlates with the site of provirus integration (7,8,21,25,26,41) and with the pattern of proviral DNA methylation acquired during gametogenesis (19).…”
mentioning
confidence: 99%
“…Under these conditions, ev-2 gives rise to an infectious virus called Rousassociated virus-0 (RAV-0); the LTRs of ev-2 and RAV-0 are identical (23,41). Previous studies have indicated that the expression of individual evs correlates with the site of provirus integration (7,8,21,25,26,41) and with the pattern of proviral DNA methylation acquired during gametogenesis (19). However, sequence analysis of the LTR of an ev that normally is expressed in vivo (ev-3) showed minor nucleotide variations relative to the LTRs of ev-1 and ev-2.…”
mentioning
confidence: 99%